Imitation - Theory and Experimental Evidence - - Jose Apesteguia; Steffen Huck; Jörg Oechssler (University of Heidelberg, Department of Economics, 2005)
We introduce a generalized theoretical approach to study imitation and subject it to rigorous experimental testing. In our theoretical analysis we find that the different predictions of previous imitation models are due to different informational assumptions, not to different behavioral rules. It is more important whom one imitates rather than how. In a laboratory experiment we test the different theories by systematically varying information conditions. We find significant effects of seemingly innocent changes in information. Moreover, the generalized imitation model predicts the differences between treatments well. The data pro- vide support for imitation on the individual level, both in terms of choice and in terms of perception. But imitation is not unconditional. Rather individuals propensity to imitate more successful actions is increasing in payoff differences.
Keywords: C72; C91; C92; D43; L13; 330; Evolutionary game theory; Stochastic stability; Imita- tion; Cournot markets; Information; Experiments; Simulations; Imitationsstrategie; Test; Duopol; Evolutionäre Spieltheorie; Theorie